Media Pembelajaran Interaktif menggunakan Metode Collaborative Learning pada Mata Pelajaran Pendidikan Kewarganegaraan - Siti Seituni; Irma Noervadila (STKIP PGRI SITUBONDO, 2022)
Abstrac: Implementation of Collaborative Learning For Student Results Subjects with the development of basic competencies of civics educatioins with base competence in Indonesia XI IPS 2 Semester Ganjil in MA Sarji Ar-Rasyid Tahun ajaran 2012/2013. There are various problems of its own in the learning process. One of the common problems is the low activity in the classroom and mastery learning students due to low student learning outcomes. of civics educatioins with base competence in Indonesia XI IPS 2 Semester Ganjil in MA Sarji Ar-Rasyid Tahun ajaran 2012/2013. The purpose of this study was to determine the yield increase by applying Collaboraive Student Learning Model Class XI IPS 2 Civics Educations Lesson In Sarji Ar-Rasyid Tahun ajaran 2012/2013. The approach used in this study is a qualitative approach , while the type of research is action research with research subjects were students of class XI IPS 2 in MA Sarji Ar-Rasyid. The data obtained were collected by the method of observation, interviews, and documentation , while the implementation began on 4 November 2013 until the date of December 4, 2013 . Based on the results of the analysis can be seen that Collaboraive Learning Model to improve academic skills and can improve cooperation among students , because the students Collaborative Learning Model may find yourself concept that should be known by the investigation of real problems . In the first cycle of mastery learning classical achieved by 83.87 % and complete student individually as many as 26 students and 5 students not complete . Factors - factors that cause incomplete study of 5 students is their lack of control of the material, less scrupulous , shy to ask , and less good at set time in doing it . In the second cycle was reached in classical mastery learning students at 87.1 % of 27 students who completed individually. Keywords: Collaborative Learning Model , Learning Outcomes